Odpowiedzi

Najlepsza Odpowiedź!
2010-01-20T17:56:14+01:00
X+2y=5
3x-y=1

x=5-2y
3(5-2y)-y=1

x=5-2y
15-6y-y=1

15-7y=1
-7y=14
y=-2

y=-2
x=5-2*-2
x=5+4
x=9

b)2x+y=7
3x-2y=0

y=7-2x
3x-2(7-2x)=0

y=7-2x
3x-14+4x=0

y=7-2y
7x=14

y=7-2y
x=2

y=3
x=2
2010-01-20T18:00:13+01:00
X=5-2y
3(5-2y)-y=1

x=5-2y
15-6y-y=1

x=5-2y
-7y=-14 / :(-7)

y=2
x=5-4

x=1
y=2

2)
2x+y=7
3x-2y=0

y=7-2x
3x-2(7-2x)=0

y=7-2x
3x-14+4x=0

y=7-2x
7x=14 / :7

x=2
y=7-4

x=2
y=3
2010-01-20T18:09:48+01:00
A)
x+2y =5
3x - y = 1
x = 5 - 2y
3(5 - 2y) - y = 1
x = 5- y
15 - 6y - y = 1
x = 5 - y
- 7y = -14
x = 5 - 2y
y = 2
x = 5 - 4
y = 2
x = 1
y =2
b)
2x + y = 7
3x - 2y = 0
y = 7 - 2x
3x - 2(7 - 2x) = 0
y = 7 - 2x
3x - (14 - 4x) = 0
y = 7 - 2x
3x - 14 +4x = 0
y = 7 - 2x
7x = 14
y = 7 - 2x
x = 2
y = 7 - 4
x = 2
y = 3